Internally displaced “Victims of Armed Conflict” in Colombia: the trajectory and trauma signature of forced migration (2014)
While conflict-induced forced migration is a global phenomenon, the situation in Colombia, South America, is distinctive. Colombia has ranked either first or second in the number of internally displaced persons for 10 years, a consequence of decades of armed conflict compounded by high prevalence of drug trafficking. The displacement trajectory for displaced persons in Colombia proceeds through a sequence of stages: (1) pre-expulsion threats and vulnerability, (2) expulsion, (3) migration, (4) initial adaptation to relocation, (5) protracted resettlement (the end point for most forced migrants), and, rarely, (6) return to the community of origin. Trauma signature analysis, an evidence-based method that elucidates the physical and psychological consequences associated with exposures to harm and loss during disasters and complex emergencies, was used to identify the psychological risk factors and potentially traumatic events experienced by conflictdisplaced persons in Colombia, stratified across the phases of displacement. Trauma and loss are experienced differentially throughout the pathway of displacement.